Crianças com autismo na educação infantil: avaliação de políticas públicas de inclusão em duas escolas da rede municipal de ensino de Fortaleza-CE (2023-2024) - Souza, Jarinete Siridó de (2025)
Special Education, framed within Inclusive Education policies, is grounded in the fundamental principle of ensuring every child's right to learn in school environments that respect their singularities. In the case of children with Autism Spectrum Disorder (ASD), challenges become more complex due to the pedagogical, formative, and institutional demands inherent in the structure of public early childhood education. This study investigates how public policies for school inclusion are materialized in practice in two schools of District IV, in the municipal education network of Fortaleza-CE, regarding the inclusion of children with autism in early childhood education. The general objective is to carry out an in-depth evaluation of public policies aimed at the inclusion of autistic children in regular early childhood education, focusing on two municipal schools in District IV. The research follows a qualitative approach, based on the in-depth evaluation methodology proposed by Rodrigues (2008), and includes direct observations, interviews with teachers, coordinators, and support professionals, as well as document analysis of relevant legal and institutional frameworks. Theoretical foundations include the works of Mantoan (2006), Teixeira (2016), Vygotsky (1991, 2012, 2019), Saviani (2009), and Rafante (2013, 2015, 2019), which supported critical reflection on inclusive and socially committed educational practices. The analyses revealed meaningful advances in the reception and participation of children with ASD, but also persistent limitations in collaborative planning, ongoing teacher training, and infrastructure. The roles of inclusion assistants and the availability of Multifunctional Resource Rooms proved essential, though uneven across schools. Municipal initiatives such as the Vincular Project, early enrollment, and expanded support services contribute positively to the inclusion process, yet require stronger intersectoral coordination. It is concluded that the effective inclusion of children with ASD depends on continuous investment, qualified listening to school actors, strong family-school partnerships, and institutional commitment to equitable pedagogical practices and transformative public policies.